(untitled) (Research, Society and Development, 2022)
Considering the essential purpose of the internship, the Federal University of Mato Grosso (UFMT) and the Court of Accounts of the State of Mato Grosso (TCE-MT) signed an agreement for the operationalization of the internship program. It is sought, in this process, that the trainee can reveal the ability to question, problematize, know and move within the scenarios of professional practices. The objective of the work was to evaluate the trainee’s learning in his professional field, within the scope of the UFMT / TCE agreement. In this process, personnel from the academy (teachers and students) and TCE-MT employees were involved. The data collection and analysis procedure took place through semi-structured interviews and through the application of a questionnaire with at least 30% of the interns of the agreement. As a triangulation of data collection, participated in the research the supervising professors and those directly responsible for the trainees at the TCE. This work involved observations, participations and interventions made during the internship, aiming to reflect on the relationship between practice and theory, along with the difficulties and challenges during this process.